2D CFD-model of the piston assembly in a diesel engine for the analysis of piston ring dynamics, mass transport and friction. (December 2016) - Lyubarskyy, Pavlo; Bartel, Dirk
Abstract: The 2D CFD-model of piston assembly was built up to analyze the mass transport through the piston-liner crevices of a diesel engine. Calculations of piston ring dynamics are performed by means of the balance of forces solved in CFD. An elastic-plastic contact model is incorporated in the CFD-model to calculate the asperity contact and boundary friction in rings/liner/grooves interfaces. The hydrodynamic friction is calculated by means of CFD. An analytical approach is implemented in 2D CFD-model to consider the mass-flow through the ring gaps allowing the estimation of inter-ring pressures and blowby into the crankcase. The 2D CFD-model can be used to study the influence of the various ring-pack design parameters on the ring friction, blowby and oil transport. Highlights: The integral 2D CFD-model of piston assembly describing ring-pack performance. Multiphase numerical simulation of mass transport and blowby through the ring-pack. Solids interactions (contact mechanics) in CFD by means of asperity contact model. Directly coupling of solid (piston rings) dynamics is with fluid dynamics (CFD). Different regimes of friction in model - hydrodynamic, mixed and boundary friction.